Foot Massage Modification to Reduce Blood Pressure in Pregnant Woman with Preeclampsia - Ermiati Ermiati; Anita Setyawati; Etika Emaliyawati (Faculty of Nursing Universitas Padjadjaran, 2018)
The Maternal Mortality Ratio (MMR) in Indonesia remains high, including in West Java province. One of the MMR causes is preeclampsia (24%). Currently, the management of preeclampsia is focused on pharmacological therapy. Preeclampsia is characterized by high blood pressure. Some studies revealed that non-pharmacological therapy was effective in dealing high blood pressure including foot massage. Foot message has benefits both physiologically and psychologically. However limited study applied this massage among pregnant women with preeclamsia. The aim of this study was to determine the effectiveness of as a complementary therapy: foot massage to reduce of blood pressure among pregnant women with preeclampsia. The study applied quasi experimental design with time series approach. The samples were chosen using consecutive sampling technique. This study involved 30 pregnant women with preeclampsia. There were two steps of data collection. First, respondents’ blood pressure was measured by researchers without any interventions for 6 days. Second, the 7th -12th respondents had 20 minutes message, and observed blood pressure at the first minute before massage (pr-etest), and the 30th minutes after massage (post-test). Data were analyzed using Friedman Test.The result showed that there were no significant differences of mean systolic and diastolic blood pressure between pre-test and post-test (p> 0.05) in control period. Whereas, in the treatment period showed that there were a significant differences of mean systolic blood pressure between pre-test and post-test on the seventh day until twelfth day (p < 0.05). While, the significantly differences in mean of diastolic blood pressure between pre-test and post-test were present during the eighth until twelfth in treatment period (p < 0.05). This study revealed that there were significant differences in decreasing of blood pressure among pregnant women with preeclampsia after treatment by foot massage. The foot massage techniques can be used as one of the interventions to lower blood pressure in pregnant women with preeclampsia, however further research is needed to support the evidence based for nursing intervention especially in complementary therapies.